2018
DOI: 10.4103/1793-5482.185065
|View full text |Cite
|
Sign up to set email alerts
|

Good outcomes with the intraventricular vancomycin therapy in a patient with ruptured brain abscesses

Abstract: Brain abscesses are associated with high morbidity and mortality rates. In particular, patients with intraventricular rupture of brain abscess (IVROBA) exhibit mortality rates up to 85%. Treatment options are lacking for IVROBA, once patients become refractory to intravenous antibiotics and surgical drainage. Limited data exist regarding the risks and benefits of intraventricular therapy in such a scenario. We report a patient with IVROBA, who deteriorated while on systemic antibiotics; once intraventricular v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Brewer et al recommended drainage as a routine therapy in a paper published in 1975 [12]. The intraventricular administration of vancomycin has been presented as a successful treatment for pyocephalus in a number of previous case studies [6,13,14] although this approach has been unsuccessful in other cases involving gentamicin [15]. Two patients died early on in our study from ongoing sepsis and multiple organ failure.…”
Section: Treatment Modalities Of Pyocephalusmentioning
confidence: 69%
See 2 more Smart Citations
“…Brewer et al recommended drainage as a routine therapy in a paper published in 1975 [12]. The intraventricular administration of vancomycin has been presented as a successful treatment for pyocephalus in a number of previous case studies [6,13,14] although this approach has been unsuccessful in other cases involving gentamicin [15]. Two patients died early on in our study from ongoing sepsis and multiple organ failure.…”
Section: Treatment Modalities Of Pyocephalusmentioning
confidence: 69%
“…Another study by the Thai authors concluded that spontaneous intraventricular rupture and fungal abscesses were predictors of a poor outcome [10]. A series of earlier case studies considered pyocephalus as a malign symptom associated with an adverse outcome [2,3,6]. In a study of 179 patients treated between 1986 and 2005, Lee et al identified the risk factors predictive of ventricular rupture to be size and multiloculation of abscesses, and their proximity to the ventricular system.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As the patient did not respond to standard intravenous antibiotic treatment and her health was deteriorating after primary intervention, we decided to treat her recurrence with vancomycin via an intracranial drain while continuing the intravenous treatment. The use of an intracranial drain as a conduit for drug administration has been shown to be a safe and viable option in other studies in the past [ 15 ]. We chose to use vancomycin rather than ceftriaxone as intrathecal administration of vancomycin has been well studied while the outcomes of intrathecal administration of ceftriaxone are not well known [ 16 ].…”
Section: Discussionmentioning
confidence: 99%